Haemodynamic Kinetics and Intermittent Finger Flexor Performance in Rock Climbers - Fryer, S.; Stoner, L.; Lucero, A.; Witter, T.; Scarrott, C.; Dickson, T.; Cole, M.; Draper, N. (International Journal of Sports Medicine, 2015)
Currently it is unclear whether blood flow (BF) or muscle oxidative capacity best governs performance during intermittent contractions to failure. The aim of this study was to determine oxygenation kinetics and BF responses during intermittent (10 s contraction: 3 s release) contractions at 40% of MVC in rock climbers of different ability (N=38). Total forearm BF, as well as de-oxygenation and re-oxygenation of the flexor digitorum profundus (FDP) and the flexor carpi radialis (FCR) were assessed. Compared to the control, intermediate and advanced groups, the elite climbers had a significantly (p<0.05) greater force time integral (FTI), MVC and MVC/kg. Furthermore, the elite climbers de-oxygenated the FDP significantly more during the first (7.8, 11.9, 12.4 vs. 15.7 O2%) and middle (7.3, 8.8, 10.4 vs.15.3 O2%) phases of contractions as well as for the FCR during the first phase only (8.3, 7, 11.7 vs. 13.3 O2%). They also had a significantly higher BF upon release of the contractions (656, 701, 764 vs. 971 mL ∙ min−1). The higher FTI seen in elite climbers may be attributable to a greater blood delivery, and an enhanced O2 recovery during the 3 s release periods, as well as a superior muscle oxidative capacity associated with the greater de-oxygenation during the 10 s contractions.
Keywords: blood flow; oxygenation; elite climbers; force time integral; climbing performance